A Novel 'Transfibular Approach' for the Nonunion of a Tibial Shaft Fracture with Poor Anteromedial Soft Tissue Cover - Vaishya, Raju (Cureus, 2015)
The need for an ideal approach for the nonunion of the tibial shaft with anteromedial soft tissue scarring has long baffled surgeons. Many different approaches have been suggested in the past, but all those approaches were haggled by a multitude of problems. We have described a novel 'transfibular approach' for this selective situation. An appropriate patient with a mid-shaft tibial non-union was selected. After preoperative workup, the patient underwent an open reduction internal fixation (ORIF) with lateral tibial plating, bone grafting, and partial fibulectomy. In this new approach, the plane between tibialis anterior and extensor hallucis longus was used combined with a conventional posterolateral approach using the same incision. Subsequently, the patient was followed up for adequacy of the fixation and wound-related problems with a convincing outcome.